2019
DOI: 10.1088/1361-6668/aafa88
|View full text |Cite
|
Sign up to set email alerts
|

Initial growth of tin on niobium for vapor diffusion coating of Nb3Sn

Abstract: Nb3Sn has the potential to achieve superior performance in terms of quality factor, accelerating gradient and operating temperature (4.2 K vs 2 K) resulting in significant reduction in both capital and operating costs compared to traditional niobium SRF accelerator cavities. Tin vapor diffusion coating of Nb3Sn on niobium appears to be a simple, yet most efficient technique so far to fabricate such cavities. Here, cavity interior surface coatings are obtained by a two step process: "nucleation" followed by "de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Several examples include coatings grown on niobium which was anodized prior to the coating. For indepth discussion of the Nb3Sn vapor deposition setup, process, and anodization refer to reference [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several examples include coatings grown on niobium which was anodized prior to the coating. For indepth discussion of the Nb3Sn vapor deposition setup, process, and anodization refer to reference [11].…”
Section: Methodsmentioning
confidence: 99%
“…[27,28] Other studies involving anodization and the nucleation process have shown mixed results. [11,29] Here we use EBSD and analysis by NIH ImageJ software to help gain insight into the structural differences between Nb3Sn grown on anodized niobium surfaces versus that grown on NP niobium surfaces. Where θF is the Feret angle and θG is the orientation angle of the grain with respect to the x-axis.…”
Section: Surface Anodization Effect On Coatingmentioning
confidence: 99%
“…Nb 3 Sn is of interest as a coating for superconducting radiofrequency (SRF) cavities due to its higher critical temperature T c of ~18.3 K and superheating field H sh of ~400 mT [1]. Nb 3 Sn cavities have the potential to achieve high quality factor Q 0 when operated at 4 K and can replace the bulk Nb cavities that are operated at 2 K [2,3]. The higher operating temperature of Nb 3 Sn cavities compared to Nb can significantly reduce the operating cost.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different intermetallic phases of the Nb-Sn system, only the A15-type Nb 3 Sn is superconducting above 10 K. However, thin film synthesis of high quality Nb 3 Sn is still a huge challenge. 2 Among the reported thin film deposition methods are tin evaporation, [3][4][5] chemical vapor deposition, 6 sputtering, [7][8][9][10][11] electron beam evaporation, 12 bronze processing, 13 and electrodeposition. 14 However, the tin diffusion process is the only process used so far for the production of cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported approaches potentially lead to inhomogeneous or graded distributions of Nb and Sn and, furthermore, to the formation of non-superconducting phases limiting the desired performance since they all require annealing. 4,17,18 Tin evaporation is the first and most advanced process for actual production of cavities. Sputtering approaches are significant as an alternative route of coating copper cavities.…”
Section: Introductionmentioning
confidence: 99%